Modeling of Flotation Process—An Overview of Different Approaches. (3rd March 2016) - Gharai, Mousumi; Venugopal, R.
ASBTRACT: The modeling of flotation has been reviewed with the aim of identifying their usefulness, significance as well as limitations. From literature it is clear that, various flotation models have been developed on the basis of the processes and sub-processes occurring in flotation. An overview of the literature indicates that various approaches have been adopted in quantifying the process. Flotation models based on kinetics have prevailed in almost all flotation conditions regardless of the ore type and ore characteristics as well as flotation cell configurations. It may be concluded that the classical first-order kinetic model is comparatively a better model and can be utilized to optimize the flotation process as it is applicable to both batch and continuous flotation processes with high confidence level. Finally, it is suggested that future work should focus on improving the models which can more accurately predict the prevailing conditions and enable better optimization of the flotation process.